2009
DOI: 10.1055/s-0029-1236834
|View full text |Cite
|
Sign up to set email alerts
|

Latissimus Dorsi/Rib Intercostal Perforator Myo-Osseocutaneous Free Flap Reconstruction in Composite Defects of the Scalp: Case Series and Review of Literature

Abstract: Adequate coverage of complex, composite scalp defects in previously radiated, infected, or otherwise compromised tissue represents a challenge in reconstructive surgery. To provide wound closure with bony protection to the brain, improve cranial contour, and prevent or seal cerebrospinal fluid (CSF) leaks, composite free tissue transfer is a reliable and safe option. We report our experience with the latissimus dorsi/rib intercostal perforator myo-osseocutaneous free flap in the reconstruction of bony and soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…7 An incision was first made at the anterior border of the latissimus dorsi muscle to identify the thoracodorsal vessels. Thoracodorsal perforators supplying the skin were identified and preserved for the skin paddle.…”
Section: Methodsmentioning
confidence: 99%
“…7 An incision was first made at the anterior border of the latissimus dorsi muscle to identify the thoracodorsal vessels. Thoracodorsal perforators supplying the skin were identified and preserved for the skin paddle.…”
Section: Methodsmentioning
confidence: 99%
“…A 100% union rate was achieved in all cases but the average time for bone union was not specified in any studies. Seitz et al reported three partial flap necrosis and one donor site complication (pneumothorax) has been observed by Lee et al…”
Section: Resultsmentioning
confidence: 90%
“…Five publications were identified that treated a total of 22 patients with a thoracodorsal based composite flap with vascularized rib for infected cranioplasty, osteomyelitis, and brain tumor. A 100% union rate was achieved in all cases but the average time for bone union was not specified in any studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations